Pendampingan Guru dalam Rangka Pengelolaan Keuangan Melalui Pelatihan “Guruku Investor Saham” - Verlandes, Yuliasnita; Fitri Isnaini, Nurdiana; Makhfuddin Akbar, Ronny; Hadi Poernomo, Agoes (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Indonesian government is in the process of campaigning stock investment through as an alternative mode of investment for the people who usually invests in fixed assets and bank deposits. Stock investment has many advantages that are often on par with other investment options. Stock investment has many advantages that are often on par with other investment options. Stock investment is also easier to do, the wide availability of smartphones facilities stock investment. Even though is has many advantages, stock investment is not widely known by people, therefore there needs to be training with regards to buying stocks and controlling the investments. As a productive group that has close ties to society and acts as agents of change, teachers are the best partners to work with for this social service. The main partner in this social service are the SMAN teachers from SMAN 1 Kutorejo. The social service started with the filling of forms in order to create a stock investment account and followed by practical training on how to buy and sell stocks. The result of this social service is the increase of the teachers “knowledge about general financial literacy and also the creation of new stock investment accounts.